Hartley Jafine: The Role of Drama in the Health Sciences - Ostrovski, Ilia; Chin, Brian; Chopra, Shelly (The Meducator, 2012)
Hartley Jafine is an instructor of theatre and arts-based courses in the Bachelor of Health Sciences program. He has studied and used applied drama—a form of theatre that is now being used as a tool for social and interpersonal skill development—as an educational medium for many years. The Meducator recently had the opportunity to interview Jafine on the effectiveness of applied drama in helping students regain their passion and health professionals understand their patients.